Sprint running kinematics and kinetics in pre-peak-height-velocity male children on a non-motorised treadmill: reliability and normative data - Rumpf, M. C.; Cronin, J.; Oliver, J.; Hughes, M. (Sports Biomechanics, 2019)
The purpose of this study was to quantify the reliability of kinematic and kinetic variables using a sample of pre-peak-height-velocity (PHV) male athletes sprinting on a non-motorised treadmill. Following variables were measured and their normative data presented, average and peak velocity, average and peak power, average and peak horizontal force, average and peak vertical force, average step frequency, average step length, average work. Twenty-five participants performed three 5-s all-out sprints from a standing split start on a non-motorised treadmill on three separate occasions. Per cent change in the means (-3.66 to 3.35%) and coefficients of variation (0.56-7.81%) were thought reliable for all variables. However, average step rate, average horizontal force and average vertical force did not meet the standards (=0.70) set for acceptable intraclass correlation coefficients (ICC). Due to the homogeneous group, it was expected to receive low ICC values. Therefore, youth sprinting performance can be tested reliably on a non-motorised treadmill, especially if the per cent change in the mean and CV are deemed the important reliability measures. Normative data are given for the participant`s age as well as their maturity level for kinematic and kinetic variables.